Efektivitas LKPD Berbasis Project-Based Learning (PjBL) Terintegrasi Kearifan Lokal Payakumbuh Terhadap Kinerja Ilmiah Peserta Didik Pada Materi Bioteknologi Fase E SMA - Elisa Aulia; Fitri Arsih; Ardi Ardi; Ganda Hijrah Selaras (LP2M UIN Ambon, 2026)
This study was conducted to analyze the effectiveness of using Project-Based Learning (PjBL)-based Student Worksheets (LKPD) linked to the local wisdom of Payakumbuh on students’ academic performance in high school Phase E biotechnology. This study employed a quasi-experimental approach with an unequal control group design. The study participants consisted of 68 students divided into an experimental class and a control class. Data were collected through pretests and posttests, which were then analyzed using normality tests, homogeneity tests, an independent samples t-test, and N-Gain analysis. The analysis results indicated that the average student score in the experimental class increased from 40.91 to 62.41, while in the control class it rose from 41.97 to 56.29. The hypothesis test yielded a significance value of 0.041 (p < 0.05), indicating a significant difference in outcomes between the two groups. The N-Gain value for the experimental class reached 36.98%, falling into the moderate category, while the control class achieved 23.98%, falling into the low category. The research results indicate that the use of PjBL-based worksheets combined with the local wisdom of Payakumbuh can provide a more meaningful learning experience and support improvements in students’ academic performance in biotechnology education.